Influence of Mixed Alkali on Fixation of Deep Shade on Single Jersey Cotton Fabrics with Reactive Dyes (Journal of Chemical Engineering, 2013)
This paper presents the influence of mixed alkali (soda ash and sodium hydroxide) on fixation of deep shades (8%, 7.6% and 7.2%) of Novacron super black G and Cottofix black B reactive dyes. The experiment explored the possibility of using the mixed alkali as a fixing agent for deep shade in the dyeing of single jersey cotton fabric instead of soda ash only. By using the proper amount of mixed alkali during dyeing, the dyed fabrics showed very good to excellent fastness properties and the process cost was reduced due to high exhaustion and fixation of dye molecule. The results showed that the reactivity of reactive dye was increased, 10% dyes was saved and the fastness of rubbing and washing were improved for each shade. DOI: http://dx.doi.org/10.3329/jce.v27i1.15860 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 58-63